Fermented soy beverages as vehicle of probiotic lactobacilli strains and source of bioactive isoflavones: A potential double functional effect - Ana Ruiz de la Bastida; Ángela Peirotén; Susana Langa; Eva Rodríguez-Mínguez; José Antonio Curiel; Juan Luis Arqués; José María Landete (Heliyon, 2023)
Soy beverages can be a source of bioactive isoflavones, with potential human health benefits. In this work, the suitability of three Lacticaseibacillus and three Bifidobacterium probiotic strains as functional starters for soy beverage fermentation were evaluated, alongside with the effect of refrigerated storage on the viability of the strains and the isoflavone composition of the fermented beverages. The three bifidobacteria strains suffered a decrease in their viability during refrigeration and only Bifidobacterium breve INIA P734 produced high concentrations of bioactive isoflavones. Meanwhile, L. rhamnosus GG and L. rhamnosus INIA P344 produced high levels of aglycones and, with L. paracasei INIA P272, maintained their viability during the refrigeration period, constituting promising starters to obtain functional soy beverages that could gather the benefits of the bioactive isoflavone aglycones and the probiotic strains. Moreover, the three lactobacilli caused an increase in the antioxidant capacity of the fermented beverages, which was maintained over the refrigerated storage.